Association between COVID-19 vaccination, SARS-CoV-2 variants, and post COVID-19 condition: A cross-sectional study - Saif-El-Din El-Akkad; Selena Shao; Karen C. Tran; Hiten Naik; Naveed Janjua; Hind Sbihi; Christopher Carlsten; James A. Russell; Adeera Levin; Alyson W. Wong (PLoS ONE, 2025)
Background Individuals may experience persistent symptoms after recovering from coronavirus disease 2019 (COVID-19), a condition referred to as post COVID-19 condition (PCC). Patient-reported outcome measures (PROMs) evaluate a patient’s health status and can be used to quantify symptom severity from the patient’s perspective. The impact of COVID-19 vaccination and variant of infection on PCC is not well understood. We therefore sought to explore vaccination and variant trends among individuals with PCC and investigate their association with abnormal PROMs. Methods Patients seen at Post-COVID-19 Clinics across British Columbia, Canada between March 2020 – Oct 2022 were included in the study. Those who had persistent symptoms, at least one abnormal PROM, and completed a baseline questionnaire within 6 months of infection were included. The following PROMs were used: Fatigue Severity Score, University of California San Diego Shortness of Breath Questionnaire, Post Traumatic Stress Disorder (PTSD) Score, Generalized Anxiety Disorder-2 and Patient Health Questionnaire-2. Vaccination status was categorized based on the number and timing of vaccinations relative to SARS-CoV-2 infection. Logistic regression was used to evaluate the association between COVID-19 vaccination status or SARS-CoV-2 variant and the likelihood of reporting abnormal PROMs. Results The study included 1,587 participants (mean age 52 ± 15 years, 45% male, 58% vaccinated). In the adjusted models, full vaccination among non-hospitalized patients was associated with a reduced likelihood of reporting PTSD. Hospitalized patients infected with the alpha and delta variants were more likely to report dyspnea, while those infected with the gamma variant were less likely to report PTSD. Conclusions Patients who were partially or fully vaccinated did not have increased risk of reporting common PCC symptoms. Infection with the alpha and delta variants was associated with increased likelihood of reporting dyspnea, which may be related to the severity of acute illness and associated impairments in lung function.